Rituximab (monoclonal anti-CD20 antibody) induced posterior reversible encephalopathy syndrome (PRES): A case report and literature review - Praveen K. Sharma, MD; Sanjaykanth Balachandar, MBBS; Michael Antony Vikram, MBBS; Pujitha Duvooru Sukumar, MD (Radiology Case Reports)
Posterior reversible encephalopathy syndrome (PRES) is an uncommon neurological condition characterized by reversible subcortical vasogenic edema that primarily affects the posterior areas of the brain. Subcortical vasogenic edema resulting from endothelial injury and hypertension is the pathogenesis. Here, we present a 23-year-old female patient with systemic lupus erythematosus (SLE) and lupus nephritis who developed PRES following Rituximab (a monoclonal anti-CD-20 antibody) administration. The patient initially presented with severe headaches, visual disturbances, and an altered mental status. Neurological examination revealed bilateral cortical blindness, hyperreflexia, and seizures. Brain imaging, including MRI, demonstrated characteristic findings of PRES, with symmetric hyperintensities involving the occipital and parietal lobes on T2-weighted and FLAIR sequences, consistent with vasogenic edema. Rituximab is promptly discontinued, and the patient was managed with supportive care, including antiepileptic drugs and blood pressure control. Within days of Rituximab cessation, the patient showed gradual improvement in symptoms, with resolution of cortical blindness and normalization of MRI findings. Follow-up assessments revealed complete neurological recovery without residual deficits. This instance emphasizes how crucial it is to take into account PRES as a possible side effect in patients receiving Rituximab therapy, especially if those individuals have sudden neurological symptoms. The offending agent must be located and eliminated immediately for the best outcomes. Clinicians should maintain a high index of suspicion for PRES in patients receiving monoclonal anti-CD20 antibody therapies, immunosuppressants, and corticosteroids, facilitating timely diagnosis and intervention to prevent potentially life-threatening complications. More studies are necessary to clarify the pathophysiological mechanisms causing the PRES produced by Rituximab and to improve therapeutic approaches.